2011
DOI: 10.2175/106143011x12928814444970
|View full text |Cite
|
Sign up to set email alerts
|

Combined Anaerobic/Aerobic Digestion: Effect of Aerobic Retention Time on Nitrogen and Solids Removal

Abstract: A combined anaerobic/aerobic sludge digestion system was studied to determine the effect of aerobic solids retention time (SRT) on its solids and nitrogen removal efficiencies. After the anaerobic digester reached steady state, effluent from the anaerobic digester was fed to aerobic digesters that were operated at 2-to 5-day SRTs. The anaerobic system was fed with a mixture of primary and secondary sludge from a local municipal wastewater treatment plant. Both systems were fed once per a day. The aerobic react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 4 publications
3
9
0
Order By: Relevance
“…This observation concurs with the findings of Shen et al (2013) and Wang et al (2014) showing the benefits of mixing food waste with FVW. Also, VS, TS and COD removal rates stabilized with averages of 83 ± 1.5%, 81 ± 1.6%, and 87 ± 1.6%, respectively, which are close to pre-inhibition rates and similar to the reported figures for mesophilic AD of FW and FVW (Ganesh et al, 2014; Kim and Novak, 2011; Serrano et al, 2014; Shen et al, 2013; Wang et al, 2014).…”
Section: Results and Analysissupporting
confidence: 86%
“…This observation concurs with the findings of Shen et al (2013) and Wang et al (2014) showing the benefits of mixing food waste with FVW. Also, VS, TS and COD removal rates stabilized with averages of 83 ± 1.5%, 81 ± 1.6%, and 87 ± 1.6%, respectively, which are close to pre-inhibition rates and similar to the reported figures for mesophilic AD of FW and FVW (Ganesh et al, 2014; Kim and Novak, 2011; Serrano et al, 2014; Shen et al, 2013; Wang et al, 2014).…”
Section: Results and Analysissupporting
confidence: 86%
“…In Scenario 1, the sequential ME-ME and TH-TH AN/ AERO configurations achieved 9.2À10.9% higher VS removals than Control 1 (ME) and Control 2 (TH), respectively. Hence, it was observed that the overall VS removal of sequential AN/ AERO process increased with an increase in SRT of AERO digesters, which supports the literature (Kim and Novak, 2011). In removal over the respective control section of Figure 3, removal of VS in TPD (TH-ME) is with respect to Control 2 (TH).…”
Section: Resultssupporting
confidence: 86%
“…As expected, the removal of ammonia by AERO digesters of sequential AN/AERO systems decreased with a decrease in SRT of AERO digesters from 5.1 (Scenario 1) to 3.4 and 1.7 d in Scenarios 2 and 3, respectively (Figure 6). Kim and Novak (2011) also suggested that ammonia removal by AERO digesters decreases with the decrease in SRT.…”
Section: Resultsmentioning
confidence: 98%
“…These conditions result in nitrogen removal without the need to provide an external carbon source and was postulated to be to the result of simultaneous nitrication and denitrication. 30 Biological processes, such as anaerobic digestion, have a known range of healthy operating conditions and loading capacities, it is necessary to identify important operational parameters for PAD to understand capability, design, and trouble-shooting approaches. Moreover, full-scale analysis is required to know real-world process capabilities for nutrient loading and removal.…”
Section: Introductionmentioning
confidence: 99%